The roles of healthcare professionals in diabetes care: a qualitative study in Norwegian general practice - Monica Sørensen; Karen Synne Groven; Bjørn Gjelsvik; Kari Almendingen; Lisa Garnweidner-Holme (Taylor & Francis Group, 2020)
Objective: To explore the experiences of general practitioners (GPs), nurses and medical secretaries in providing multi-professional diabetes care and their perceptions of professional roles. Design, setting and subjects: Semi-structured interviews were conducted with six GPs, three nurses and two medical secretaries from five purposively sampled diabetes teams. Interviews were analysed thematically. Main outcome measures: Healthcare professionals' (HCPs') experiences of multi-professional diabetes care in general practice. Results: The involvement of nurses and medical secretaries (collaborating health care professionals) was mainly motivated by GPs' time pressure and their perception of diabetes care as easy to standardize. GPs reported that diabetes care had become more structured and continuous after the involvement of collaborating health care professionals (cHCPs). cHCPs defined their role differently from GPs, emphasizing that their approach included acknowledging patients' need for diabetes education, listening to their stories and meeting their need for emotional support. GPs appeared less involved in patients' emotional concerns and more focused on the biomedical aspects of illness. There was little emphasis on teamwork among GPs and cHCPs, and none of the practices used care plans to involve patients in decisions or unify treatment among professionals. Participants stated that institutional structures including a discriminatory remuneration system, lack of role descriptions and missing procedures for collaborative approaches were an obstacle to MPC. Conclusions: cHCPs worked independently under delegated leadership of the GPs. Although cHCPs had a complementary role, HCPs in general practice may not take full advantage of the potential of sharing patient responsibility and learning with, from and about each other. Contextual barriers for team-based care approaches should be addressed in future research.KEY POINTS It has been suggested that multi-professional approaches improve quality of care in people with long-term conditions. In this study, nurses and medical secretaries perceived to have a complementary role to general practitioners (GPs) in diabetes care, focusing on patient education, building trusting relationships and providing patients with emotional support. As multi-professional collaboration was minimal, GPs, nurses and medical secretaries in the included practices may not take full advantage of the potential of sharing care responsibility and learning with, from and about each other.